Neanderthal diet at Vindija and Neanderthal predation : the evidence from stable isotopes - Richards, Michael P.; Pettitt, Paul B.; Trinkaus, Erik Smith, Fred H.; Paunović, Maja Karavanić, Ivor (2000)
Archeological analysis of faunal remains and of lithic and bone
tools has suggested that hunting of medium to large mammals was
a major element of Neanderthal subsistence. Plant foods are
almost invisible in the archeological record, and it is impossible to
estimate accurately their dietary importance. However, stable
isotope ( d 13 C and d 15 N) analysis of mammal bone collagen provides
a direct measure of diet and has been applied to two Neanderthals
and various faunal species from Vindija Cave, Croatia. The isotope
evidence overwhelmingly points to the Neanderthals behaving as
top-level carnivores, obtaining almost all of their dietary protein
from animal sources. Earlier Neanderthals in France and Belgium
have yielded similar results, and a pattern of European Neander-thal
adaptation as carnivores is emerging. These data reinforce
current taphonomic assessments of associated faunal elements
and make it unlikely that the Neanderthals were acquiring animal
protein principally through scavenging. Instead, these findings
portray them as effective predators.
Projekt MZOS
Projekt MZOS
ENG